Battery and electric equipment with same
Patent Information
- Application Number
- CN202380060353.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-09
- Publication Date
- 2025-03-28
AI Technical Summary
When ternary materials are mixed with lithium-manganese materials, due to different voltages and material properties, processing problems such as gelling, clogging of filter elements, and poor particle dispersion can occur, affecting the energy density and service life of the battery.
A multiple cell parallel structure is adopted, in which the first cell uses ternary material as the positive electrode material, and the second cell uses lithium-containing phosphate material to avoid direct mixing of materials and improve the energy density and cycle life of the battery.
It effectively avoids processing problems caused by mixing, improves the energy density and cycle life of the battery, and takes into account the safety of the battery core.
Smart Images

Figure CN119731832A_ABST
Abstract
Description
Battery and electrical equipment having the same Technical Field
[0001] The present application relates to the field of battery technology, and in particular, to a battery and an electrical device having the same. Background Art
[0002] When ternary materials are mixed with lithium manganese materials, various processing problems such as gelation, filter clogging, and poor particle dispersion will occur due to the different operating voltages and material properties of the two materials, affecting the energy density and service life of the battery.
[0003] Therefore, current batteries still need further improvement.
[0004] Summary of the Invention
[0005] The present application aims to solve one of the technical problems in the related art at least to a certain extent.
[0006] In one aspect of the present application, a battery is provided, comprising: a first battery cell, the first battery cell comprising a first positive electrode sheet, the first positive electrode sheet comprising a first positive electrode active layer, the first positive electrode active layer comprising a first positive electrode material; a second battery cell, the second battery cell comprising a second positive electrode sheet, the second positive electrode sheet comprising a second positive electrode active layer, the second positive electrode active layer comprising a second positive electrode material; the first battery cell and the second battery cell are connected in parallel; the first positive electrode material comprises a ternary material, and the second positive electrode material comprises a lithium-containing phosphate. This extends the cycle life of the battery and improves its energy density.
[0007] According to some embodiments of the present application, the number of the first battery cells is x1, the number of the second battery cells is x2, the gram capacity of the first positive electrode sheet in each of the first battery cells is amA·h / g, the gram capacity of the second positive electrode sheet in each of the second battery cells is bmA·h / g, and 0.1≤(b / a) is satisfied. 2 (x2 / x1)≤10.
[0008] According to some embodiments of the present application, 0.1≤x1 / x2≤10.
[0009] According to some embodiments of the present application, 150 mA·h / g≤a≤230 mA·h / g; and / or 100 mA·h / g≤b≤160 mA·h / g.
[0010] According to some embodiments of the present application, the lithium-containing phosphate includes Li a1 A b1 MP 1-c1 C c1 O 4-d1 D d1, wherein the A includes one or more elements of Group IA elements, the M includes VIIB elements and at least one of doping elements of the VIIB elements, the C includes one or more elements of Group IIIA elements, Group IVA elements, Group VA elements and Group VIA elements, the D includes one or more elements of Group VIA elements and Group VIIA elements, the a1 is selected from the range of 0.9 to 1.1, the b1 is selected from the range of 0 to 0.1, the c1 is selected from the range of 0 to 0.1, and the d1 is selected from the range of 0 to 0.1.
[0011] According to some embodiments of the present application, the lithium-containing phosphate includes Li a1 A b1 Mn 1-e1 E e1 P 1-c1 C c1 O 4-d1 D d1 , wherein the A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo, and W, the E includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge, the C includes one or more elements selected from the group consisting of B (boron), S, Si, and N, the D includes one or more elements selected from the group consisting of S, F, Cl, and Br, the a1 is selected from any value within the range of 0.9 to 1.1, the b1 is selected from any value within the range of 0-0.100, the c1 is selected from any value within the range of 0.001-0.100, the d1 is selected from any value within the range of 0.001 to 0.1, and the e1 is selected from any value within the range of 0.001 to 0.5.
[0012] According to some embodiments of the present application, the lithium-containing phosphate includes Li 1+x Mn 1-e1 E e1 P 1-c1 C c1 O4, wherein 1+x=a1, x is any value in the range of -0.100-0.100, e1 is any value in the range of 0.001-0.500, c1 is any value in the range of 0.001-0.100, the E includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and the C includes one or more elements selected from B (boron), S, Si and N.
[0013] According to some embodiments of the present application, the second positive electrode material includes a core and a shell covering at least a portion of the surface of the core, and the core includes the lithium-containing phosphate.
[0014] According to some embodiments of the present application, the ternary material is Li a2 Ni b2 Co c2 M1 d2 M2 e2 O f2 R′ g2 , where: 0.75 ≤ a2 ≤ 1.2, 0 < b2 < 1, 0 < c2 < 1, 0 < d2 < 1, 0 ≤ e2 ≤ 0.2, 1 ≤ f2 ≤ 2.5, 0 ≤ g2 ≤ 1, f2 + g2 ≤ 3, M1 includes Mn and / or Al, M2 includes at least one of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R′ includes at least one of N, F, S, Cl.
[0015] According to some embodiments of the present application, the ternary material includes at least one of lithium nickel cobalt aluminate and lithium nickel cobalt manganate.
[0016] According to some embodiments of the present application, based on the total mass of the first positive electrode sheet, by mass percentage: Ni 30% - 99.5%; Co 3% - 49.5%.
[0017] According to some embodiments of the present application, the ternary material is single crystal, and the particle size of the single crystal is 0.2 μm ≤ D v 50 ≤ 10 μm, D v 99 ≤ 18 μm.
[0018] According to some embodiments of the present application, the ternary material is secondary particles formed by aggregation of primary particles, the particle size of the primary particles is 50 nm - 800 nm, and the particle size of the secondary particles is 4 μm ≤ D v 50 ≤ 13 μm, D v 99 ≤ 30 μm.
[0019] According to some embodiments of the present application, the BET of the ternary material is 0.4 - 1.5 m 2 / g.
[0020] According to some embodiments of the present application, the second positive electrode material is single crystal, and the particle size of the second positive electrode material is 50 nm - 1000 nm.
[0021] According to some embodiments of the present application, the second positive electrode material is secondary particles formed by aggregation of primary particles, and the particle size of the secondary particles is 0.8 μm ≤ D v 50 ≤ 4.2 μm, D v 99 ≤ 30 μm.
[0022] According to some embodiments of the present application, the BET of the second positive electrode material is 8 - 20 m2 / g.
[0023] In another aspect of the present application, an electrical device is provided, comprising the aforementioned battery. This device thus possesses all the features and advantages of the aforementioned battery, which will not be elaborated upon here. In general, it at least has the advantage of high energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0025] FIG1 shows a schematic diagram of the arrangement of cells inside a battery according to an embodiment of the present application;
[0026] FIG2 shows a schematic diagram of the arrangement of cells inside a battery according to another embodiment of the present application;
[0027] FIG3 shows a schematic diagram of the arrangement of internal battery cells according to another embodiment of the present application.
[0028] Reference numerals:
[0029] 1000: battery; 1100: first battery cell; 1200: second battery cell. DETAILED DESCRIPTION
[0030] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this area or according to the product specifications. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0031] In one aspect of the present application, a battery 1000 is proposed. Referring to Figures 1 to 3, the battery 1000 includes a first battery cell 1100 and a second battery cell 1200. The first battery cell 1100 and the second battery cell 1200 are connected in parallel. The first battery cell 1100 includes a first positive electrode plate, a first negative electrode plate, a first separator and a first electrolyte. The first positive electrode plate includes a first positive electrode active layer, the first positive electrode active layer includes a first positive electrode material, and the first positive electrode material includes a ternary material; the second battery cell 1200 includes a second positive electrode plate, a second negative electrode plate, a second separator and a second electrolyte. The second positive electrode plate includes a second positive electrode active layer, the second positive electrode active layer includes a second positive electrode material, and the second positive electrode material includes a lithium-containing phosphate. Thus, the first positive electrode sheet and the first negative electrode sheet form the first battery cell 1100, and the second positive electrode sheet and the second negative electrode sheet form the second battery cell 1200, which can avoid processing problems caused by direct mixing of the first positive electrode material and the second positive electrode material, extend the cycle life of the battery 1000, and improve the energy density of the battery 1000.
[0032] The following is a detailed description of the principle by which this application can achieve the above beneficial effects:
[0033] Ternary materials have the advantage of high energy density when used as positive electrode active materials, but layered transition metal oxides face material losses such as phase change, Li-Ni mixing, oxygen release, and structural collapse during cycling, resulting in a short lifespan. Lithium manganese materials have the advantages of strong stability, good cycling stability, and long lifespan, but their energy density is relatively low. A mixture of ternary and lithium manganese materials as the positive electrode active material of battery 1000 can fully utilize the advantages of both. However, as mentioned above, due to the different operating voltages and material properties of the two materials, various processing problems such as gelation, filter clogging, and poor particle dispersion may occur after mixing the two materials. The battery 1000 proposed in this application includes a plurality of first battery cells 1100 and a plurality of second battery cells 1200. The positive electrode material in the first battery cells 1100 comprises the ternary material, and the positive electrode material in the second battery cells 1200 comprises lithium manganese phosphate. The two materials are assembled into battery cells separately and then assembled into battery 1000. This eliminates the need to mix the two positive electrode materials, thus avoiding the problems of gelation, filter clogging, and poor particle dispersion caused by mixing. At the same time, the positive electrode active material in the battery 1000 includes both the ternary material and the lithium-containing phosphate material, which can improve the energy density of the battery 1000 and extend the cycle life of the battery 1000.
[0034] According to some embodiments of the present application, the number of first battery cells 1100 is x1, the number of second battery cells 1200 is x2, the gram capacity of the first positive electrode sheet in each first battery cell 1100 is amA·h / g, the gram capacity of the second positive electrode sheet in each second battery cell 1200 is bmA·h / g, and 0.1≤(b / a) is satisfied.2 (x2 / x1)≤10. Preferably, 0.3≤(b / a) 2 (x2 / x1)≤3. Thus, the safety of the battery cell is improved while ensuring the energy density of the battery cell.
[0035] According to some embodiments of the present application, when the number of the first battery cell 1100 and the second battery cell 1200 satisfies the above relationship, the specific number of the first battery cell 1100 and the second battery cell 1200 is not limited. The number of the first battery cell 1100 can be greater than the number of the second battery cell 1200 (see Figure 1); or the number of the first battery cell 1100 and the number of the second battery cell 1200 are the same (see Figure 2); or the number of the second battery cell 1200 is greater than the number of the first battery cell 1100 (see Figure 3). Specifically, x1 and x2 satisfy: 0.1≤x1 / x2≤10. For example, x1 / x2 can be 1, 2, 3, 4, 5, 6, 7, 8, 9, etc. Preferably, x1 / x2 is 0.25 to 4. In this way, both the energy density and service life of the battery 1000 can be taken into account.
[0036] Specifically, 150 mA·h / g ≤ a ≤ 230 mA·h / g, for example, a may be 160 mA·h / g, 170 mA·h / g, 180 mA·h / g, 190 mA·h / g, 200 mA·h / g, 210 mA·h / g, 220 mA·h / g, etc.; and / or 100 mA·h / g ≤ b ≤ 160 mA·h / g, for example, b may be 110 mA·h / g, 120 mA·h / g, 130 mA·h / g, 140 mA·h / g, 150 mA·h / g, etc. Thus, the energy density of the battery 1000 is further increased, and the safety of the battery 1000 is improved.
[0037] The lithium phosphate material in this application is described in detail below:
[0038] According to some embodiments of the present application, the lithium-containing phosphate includes Li a1 A b1 MP 1-c1 C c1 O 4-d1 D d1 , wherein A includes one or more elements of Group IA elements, M includes VIIB elements and at least one doping element of VIIB elements, C includes one or more elements of Group IIIA elements, Group IVA elements, Group VA elements and Group VIA elements, D includes one or more elements of Group VIA elements and Group VIIA elements, a1 is selected from the range of 0.9 to 1.1, b1 is selected from the range of 0 to 0.1, c1 is selected from the range of 0 to 0.1, and d1 is selected from the range of 0 to 0.1.
[0039] Furthermore, the lithium-containing phosphate includes Li a1A b1 Mn 1-e1 E e1 P 1-c1 C c1 O 4-d1 D d1 , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo, and W, E includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge, C includes one or more elements selected from the group consisting of B (boron), S, Si, and N, D includes one or more elements selected from the group consisting of S, F, Cl, and Br, a1 is selected from any value within the range of 0.9 to 1.1, b1 is selected from any value within the range of 0-0.100, c1 is selected from any value within the range of 0.001-0.100, d1 is selected from any value within the range of 0.001 to 0.1, and e1 is selected from any value within the range of 0.001 to 0.5. Therefore, the present application can obtain significantly improved rate performance by doping specific elements in specific amounts at the Li position, Mn position, P position and O position of the compound LiMnPO4 at the same time, while significantly reducing the dissolution of Mn and the doping elements at the Mn position, obtaining significantly improved cycle performance and / or high-temperature stability, and the gram capacity and compaction density of the material can also be improved.
[0040] Furthermore, lithium-containing phosphates include Li 1+x Mn 1-e1 E e1 P 1-c1 C c1 O4, wherein 1+x=a1, x is any value in the range of -0.100 to 0.100, e1 is any value in the range of 0.001 to 0.500, c1 is any value in the range of 0.001 to 0.100, E includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and C includes one or more elements selected from B (boron), S, Si and N.
[0041] According to some embodiments of the present application, the second positive electrode material includes a core and a shell covering at least a portion of the surface of the core, wherein the core includes a lithium-containing phosphate. Specifically, the shell includes a first coating layer covering the core and a second coating layer covering the first coating layer, wherein the first coating layer includes pyrophosphate WP2O7 and phosphate XPO4, wherein W and X are each independently selected from one or more of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, or Al; and the second coating layer includes carbon.
[0042] Thus, the second positive electrode active material of the present application can improve the specific capacity, cycling performance and safety performance of the battery. Although the mechanism is not yet clear, it is speculated that the second positive electrode active material of the present application has a core-shell structure, in which by doping element E and element C at the manganese site and phosphorus site of the lithium manganese phosphate core respectively, not only can the manganese dissolution be effectively reduced, thereby reducing the manganese ions migrating to the negative electrode, reducing the electrolyte consumed due to the decomposition of the SEI film, improving the cycling performance and safety performance of the battery, but also can promote the adjustment of the Mn-O bond, reduce the lithium ion migration barrier, promote the lithium ion migration, and improve the rate performance of the battery; by coating the core with a first coating layer including pyrophosphate and phosphate, the migration resistance of manganese can be further increased, its dissolution can be reduced, the surface lithium impurity content can be reduced, and the contact between the core and the electrolyte can be reduced, thereby reducing the interfacial side reaction and gas generation, and improving the high-temperature storage performance, cycling performance and safety performance of the battery; by further coating a carbon-containing layer as the second coating layer, the safety performance and kinetic performance of the battery can be further improved.
[0043] The ternary material in the present application will be introduced in detail below:
[0044] According to some embodiments of the present application, the ternary material is Li a2 Ni b2 Co c2 M1 d2 M2 e2 O f2 R′ g2 , where: 0.75 ≤ a2 ≤ 1.2, 0 < b2 < 1, 0 < c2 < 1, 0 < d2 < 1, 0 ≤ e2 ≤ 0.2, 1 ≤ f2 ≤ 2.5, 0 ≤ g2 ≤ 1, f2 + g2 ≤ 3, M1 includes Mn and / or Al, M2 includes at least one of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R′ includes at least one of N, F, S, Cl.
[0045] Specifically, the ternary material includes at least one of lithium nickel cobalt aluminate and lithium nickel cobalt manganate.
[0046] According to some embodiments of the present application, based on the total mass of the ternary material, by mass percentage: the content of Ni can be 30% - 99.5%; the content of Co can be 3% - 49.5%. Further, the content of Ni can be 60% - 88%; the content of Co can be 5% - 35%. Thus, by controlling the Ni content within the above range, the energy density of the battery 1000 can be further improved; by controlling the Co content within the above range, the electronic conductivity and ionic conductivity of the ternary material can be further improved, effectively improving the kinetic performance of the ternary material.
[0047] According to some specific embodiments of the present application, the ternary material is a single crystal, and the particle size of the single crystal is 0.2 μm ≤ D v 50≤10μm, D v 99≤18μm. Therefore, the particle size of the ternary material is small, which helps to shorten the lithium ion diffusion path and bulk diffusion impedance, reduce the polarization of the material, and improve the energy density of the battery 1000.
[0048] When the particle size of the material is small, the surface energy is large, and the particles are easily agglomerated through interaction. According to some specific embodiments of the present application, the ternary material can also be a secondary particle formed by the agglomeration of primary particles, the particle size of the primary particles is 50nm to 800nm, and the particle size of the secondary particles is 4μm≤D v 50≤13μm, D v 99≤30μm. As a result, the particle size of the primary particles inside the secondary particles is smaller, which can further shorten the lithium ion diffusion path and bulk diffusion impedance, reduce the polarization of the material, and improve the energy density of the battery 1000.
[0049] According to some specific embodiments of the present application, the BET of the ternary material is 0.4 to 1.5 m 2 / g. That is to say, when the ternary material is a single crystal particle or a secondary particle, the BET of the ternary material is 0.4m 2 / g~1.5m 2 / g, for example, it can be 0.6m 2 / g, 0.8m 2 / g, 1.0m 2 / g, 1.2m 2 / g, 1.4m 2 / g, etc. Therefore, the compactness of the ternary material is controlled to avoid poor compaction when the ternary material is a core-shell structure or a hollow material, which leads to low overall compaction of the mixed system and reduced energy density.
[0050] Similarly, according to some specific embodiments of the present application, the second positive electrode material can also be a single crystal, and the particle size of the second positive electrode material is 50nm to 1000nm, for example, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, etc. As a result, the particle size of the second positive electrode material is relatively small, which helps to shorten the lithium ion diffusion path and bulk diffusion resistance in the second positive electrode material, reduce the polarization of the material, and improve the energy density of the battery 1000.
[0051] According to some specific embodiments of the present application, the second positive electrode material can also be secondary particles formed by agglomeration of primary particles, and the particle size of the secondary particles is 0.8 μm ≤ D v 50≤4.2μm, D v99≤30μm. This can further shorten the lithium ion diffusion path and bulk diffusion resistance, reduce the polarization of the material, and improve the energy density of the battery 1000.
[0052] According to some embodiments of the present application, the BET of the second cathode material is 8 to 20 m 2 Thus, the compactness of the secondary particles is controlled to avoid poor compaction of some core-shell structures and hollow materials, which leads to low overall compaction of the material and improves the energy density of the battery 1000.
[0053] According to some specific embodiments of the present application, the battery 1000 proposed in the present application includes two battery cells, and the negative electrode plate in the battery 1000 includes a first negative electrode plate and a second negative electrode plate. It should be noted that the first negative electrode plate and the second negative electrode plate may be the same or different. In order to simplify the preparation process of the battery 1000, the same negative electrode plate may be used in different battery cells. Specifically, the negative electrode plate generally includes a negative electrode current collector and a negative electrode active layer located on the surface of the negative electrode current collector, and the negative electrode active layer generally includes a negative electrode active material. The negative electrode active material can be various materials in the art that are suitable for negative electrode active materials of electrochemical energy storage devices. For example, it can be a combination of one or more including but not limited to graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microbeads, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Graphite can be selected from a combination of artificial graphite, natural graphite, and modified graphite; silicon-based materials can be selected from a combination of elemental silicon, silicon oxides, silicon-carbon composites, and silicon alloys; and tin-based materials can be selected from a combination of elemental tin, tin oxides, and tin alloys. The negative electrode current collector is typically a structure or component that collects current. The negative electrode current collector can be any material suitable for use as a negative electrode current collector in electrochemical energy storage devices. For example, the negative electrode current collector can include, but is not limited to, metal foil, and more specifically, copper foil. Furthermore, the negative electrode plate can also be a lithium plate.
[0054] According to some embodiments of the present application, the components of the first electrolyte and the second electrolyte may be the same or different. In order to simplify the preparation process of the battery 1000, the same electrolyte may be used in different battery cells. Specifically, when the battery 1000 is a lithium-ion battery 1000, a non-aqueous electrolyte is generally used. As a non-aqueous electrolyte, a lithium salt solution dissolved in an organic solvent is generally used. The lithium salt may be an inorganic lithium salt such as LiClO4, LiPF6, LiBF4, LiAsF6, LiSbF6, or LiCF3SO3, LiCF3CO2, Li2C2F4(SO3)2, LiN(CF3SO2)2, 9LiC(CF3SO2)3, LiC n F 2n+1SO3 (n ≥ 2) and other organic lithium salts. The organic solvent used in the non-aqueous electrolyte can be a cyclic carbonate such as ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, a chain carbonate such as dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, a chain ester such as methyl propionate, a cyclic ester such as γ-butyrolactone, a chain ether such as dimethoxyethane, diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, a cyclic ether such as tetrahydrofuran, 2-methyltetrahydrofuran, a nitriles such as acetonitrile, propionitrile, or a mixture of these solvents.
[0055] According to some embodiments of the present application, the first separator and the second separator can be the same or different. To simplify the manufacturing process of the battery 1000, the same separator can be used in different battery cells. Specifically, the separator can be selected from polyethylene film, polypropylene film, polyvinylidene fluoride film, and multilayer composite films thereof.
[0056] In another aspect of the present application, an electrical device is provided, comprising the aforementioned battery 1000. Thus, the electrical device has all the features and advantages of the aforementioned battery 1000, which will not be described in detail here. In general, it has at least the advantage of high energy density.
[0057] 1. Preparation of positive electrode sheet
[0058] The ternary material, conductive carbon, and binder polyvinylidene fluoride (PVDF) are thoroughly stirred and mixed in an appropriate amount of N-methylpyrrolidone (abbreviated as NMP) solvent at a weight ratio of 96:2:2 to form a uniform positive electrode slurry; this slurry is coated on the positive electrode current collector Al foil, and after drying, the electrode is cold pressed to the designed density and separated into strips for standby use to obtain the first positive electrode sheet.
[0059] Lithium iron phosphate, conductive carbon, and binder polyvinylidene fluoride (PVDF) are thoroughly stirred and mixed in an appropriate amount of NMP solvent at a weight ratio of 95:3:2 to form a uniform positive electrode slurry; this slurry is coated on the positive electrode current collector Al foil, and after drying, the electrode is cold pressed to the designed density and separated into strips for standby use to obtain the second positive electrode sheet.
[0060] 2. Prepare electrolyte
[0061] The electrolyte used was 1 mol / L LiPF6 / (ethylene carbonate (EC) + diethyl carbonate (DEC) + dimethyl carbonate (DMC)) (volume ratio 1:1:1) + 5 wt% fluoroethylene carbonate (FEC).
[0062] 3. Preparation of negative electrode sheet
[0063] The negative electrode active material graphite, conductive carbon, and binder sodium carboxymethyl cellulose (CMC-Na) are fully stirred and mixed in an appropriate amount of water solvent at a weight ratio of 95:3:2 to form a uniform negative electrode slurry; this slurry is coated on the negative electrode current collector Cu foil, and after drying, the electrode is cold pressed to the designed density and separated into strips for later use.
[0064] 4. Provide isolation film
[0065] PE film is selected as the isolation film.
[0066] 5. Prepare the battery
[0067] Through conventional battery manufacturing process, the first battery cell: the first positive electrode sheet (compacted density: 3.4g / cm 3 ), separator and negative electrode sheet (compacted density: 1.6g / cm 3 ) are wound together to form a bare battery cell;
[0068] Second cell: Place the second positive electrode sheet (compacted density: 2.4 g / cm 3 ), separator and negative electrode sheet (compacted density: 1.6g / cm 3 ) are wound together to form a bare battery cell; the first battery cell and the second battery cell are respectively placed in a battery casing, and an electrolyte is injected, followed by sealing, formation and other processes to finally obtain a lithium-ion secondary battery (hereinafter referred to as a battery).
[0069] Performance testing methods
[0070] 1. Battery energy density test
[0071] The capacity, nominal voltage, and mass of the secondary battery are tested separately. The mass energy density can be calculated using the following formula: mass energy density = capacity × voltage / mass. The mass can be measured using a balance (such as the JA31002 balance). The mass can be accurate to 0.1g.
[0072] 2. Test method for capacity and nominal voltage of secondary batteries:
[0073] At 25°C, the secondary battery is fully charged and then fully discharged at a charge / discharge rate of 0.33C. The measured third discharge capacity is the secondary battery capacity. The voltage corresponding to half the discharge capacity is the nominal voltage. The test process is as follows: 1) Constant current charge at a rate of 0.33C to the upper cutoff voltage, followed by constant voltage charge until the current is <0.05C; 2) Allow to stand for 10 minutes; 3) Discharge at a constant current of 0.33C to the lower cutoff voltage. The discharge capacity at this point is recorded as the secondary battery capacity, and the voltage corresponding to half the discharge capacity is the nominal voltage. Relevant terminology and test methods refer to GB / T 19596, GB / T 31484-2015, GB / T31485-2015, GB / T 31486-2015, and "Safety Requirements for Power Batteries for Electric Vehicles." Testing can be performed using equipment known in the art, such as a cell charger / discharger and a high / low temperature chamber.
[0074] 3. Lithium-ion battery 25°C power @ 10% SOC test method
[0075] Use a battery charger and discharger combined with a high and low temperature chamber to test the assembled battery's power performance at a specified temperature and SOC. Refer to GB / T 19596 and GB / T 31486 for relevant terminology and test methods.
[0076] 4. Discharge capacity test of secondary batteries
[0077] At 25°C, let the secondary battery stand for 30 minutes, then discharge it at a constant current of 0.33C to the lower cut-off voltage. Let it stand for 5 minutes, then charge it at a constant current of 0.33C to the upper cut-off voltage. Then charge it at a constant voltage until the current is less than 0.05C, let it stand for 5 minutes, and then discharge it at a constant current of 0.33C to the lower cut-off voltage. Record the discharge capacity at this time, which is the initial discharge capacity C0.
[0078] Update the discharge current of the secondary battery to 2C according to the above method and record the discharge capacity C n The 2C discharge capacity of the secondary battery is C n / C0×100%, the discharge capacity of other rates is the same.
[0079] 5. Particle size test method
[0080] The Malvern 3000 laser particle size analyzer was preheated for 30 minutes, the hydro2000sm small injection tower was selected, and it was connected to the laser particle size analyzer. An appropriate amount of clean water was added to the sampler, and the stirrer speed was turned on to 3000 rpm. The sample was cleaned for 3-5 seconds and the cleaning was repeated ≥3 times. After cleaning, an appropriate amount of pure water was added to the sample pool. After removing the bubbles, the stirrer was adjusted to 3000 rpm at a uniform speed. The stirrer speed was adjusted to the highest speed and then zeroed and waited for 3-5 seconds. The operation was repeated ≥2 times. A 50ml beaker was taken, 30ml of ultrapure water was added to it, and the sample was thoroughly mixed with 6g of sample. The sample was then placed in the ultrasonic instrument for dispersion for 5 minutes. The ultrasonic power was 60W and the measurement time was 6s. The shading was set to 8%-12%. The measurement was repeated 3 times, and the last data was taken as the particle size of the material.
[0081] 6. Inductively coupled plasma technology (ICP) testing of Ni and Co content in ternary materials:
[0082] Take about 0.4g of the dried positive electrode sheet and add 10ml of aqua regia, then place it on a hot plate and heat it to 180℃. Let it stand for 30 minutes. After the positive electrode sheet is digested, cool it to room temperature and transfer it to a 100ml volumetric flask and make it up to volume. Take 1ml of the sample and dilute it to 100ml. Perform ICP testing to obtain the content of Ni and Co elements.
[0083] Screening of the number of first and second cells in the battery and the gram capacity of the electrode
[0084] The parameters of the batteries in Examples 1 to 13 and Comparative Examples 1 to 2 are shown in Table 1. The ternary materials in the Examples and Comparative Examples are LiNi 0.5 Co 0.2 Mn 0.3 O2, the second positive electrode material is LiFe 0.5 Mn 0.5 PO4, the performance test results of the batteries in Examples 1 to 13 and Comparative Examples 1 to 2 are shown in Table 2:
[0085] Table 1
[0086]
[0087]
[0088] Table 2
[0089] Battery energy density / Wh / kg25℃Battery 10% SOCPower capabilityHot box failure temperature / ℃Comparative example 11601298230Comparative example 2240476150Example 11681375183Example 21761444180Example 31841436178Example 41921438176Example 52001361173Example 62081223170Example 7216964166Example 8224791161Example 9232569156Example 10175817195Example 11225871133Example 12177953185Example 13211968151
[0090] As can be seen from Table 2, referring to Comparative Example 2, when the battery includes only the first cell, the battery energy density is high, the battery 10% SOC power capacity at 25°C is low, and the hot box failure temperature is low; referring to Comparative Example 1, when the battery includes only the second cell, the battery energy density is low, the battery 10% SOC power capacity at 25°C is high, and the hot box failure temperature is high; referring to Examples 1 to 13, when the battery contains both the first cell and the second cell, the battery energy density, the battery 10% SOC power capacity at 25°C, and the hot box failure temperature can be optimized simultaneously. Referring to Examples 2 to 8, when the ratio of the number of the second cell to the first cell in the battery is 0.25 to 4, the overall performance of the battery is better. While ensuring the energy density, the battery 10% SOC at 25°C is high, and the hot box failure temperature can also be increased accordingly; referring to Example 5, when the ratio of the number of the second cell to the number of the first cell is 1, the overall performance of the battery is optimal.
[0091] Particle size screening when the second cathode material is secondary particles
[0092] The parameters and test results of the batteries in Examples 14 to 19 are shown in Tables 3 and 4:
[0093] Table 3
[0094]
[0095] Table 4
[0096]
[0097] As can be seen from the table above, as the particle size of the second cathode material increases, the battery's 2C discharge capacity decreases. When the particle size of the second cathode material is 10μm, the battery's 2C discharge capacity is lowest. This indicates that smaller particle size of the second cathode material helps shorten the lithium ion diffusion path and bulk diffusion resistance in the second cathode material, thereby increasing the battery's energy density.
[0098] Screening of Ni and Co mass percentage in ternary materials
[0099] The parameters and test results of the batteries in Examples 20 to 28 are shown in Tables 5 to 7:
[0100] Table 5
[0101] First positive electrode material Second positive electrode material
[0102] Example 20LiNi 0.3 Co 0.3 Mn 0.4 O2LiFe 0.5 Mn 0.5 PO4 Example 21LiNi 0.5 Co 0.1 Mn 0.4 O2LiFe 0.5 Mn 0.5 PO4 Example 22LiNi 0.82 Co 0.1 Mn 0.08 O2LiFe 0.5 Mn 0.5 PO4 Example 23LiNi 0.3 Co 0.1 Mn 0.6 O2LiFe 0.5 Mn 0.5 PO4 Example 24LiNi 0.3 Co 0.5 Mn 0.2 O2LiFe 0.5 Mn 0.5 PO4 Example 25LiNi 0.3 Co 0.02 Mn 0.6 O2LiFe 0.5 Mn 0.5 PO4 Example 26LiNi 0.3 Co 0.6 Mn 0.1 O2LiFe 0.5 Mn 0.5 PO4 Example 27LiNi 0.2 Co 0.3 Mn 0.5 O2LiFe 0.5 Mn 0.5 PO4 Example 28LiNi 0.995 Co 0.002 Mn 0.002 O2LiFe 0.5 Mn 0.5 PO4
[0103] Table 6
[0104]
[0105] Table 7
[0106] Mass percentage of Ni Mass percentage of Co Gram capacity mA·h / g2C discharge capacity Example 20 30.00% 30.00% 15585% Example 21 50.00% 10.00% 17071% Example 22 82.00% 10.00% 20565% Example 23 30.00% 10.00% 15067% Example 24 30.00% 50.00% 15888% Example 25 30.00% 2.00% 13043% Example 26 30% 60% 16055% Example 27 20% 30% 15044% Example 28 99.5% 0.2% 23530%
[0107] It can be seen from Table 7 that in Examples 20 to 24, the mass percentage of Ni is between 30% and 99.5%, and the mass percentage of Co is between 3% and 50%, and the 2C discharge capacity of the battery is greater than 65%. It can be seen from Examples 25 to 28 that when the mass percentage of Co and the mass percentage of Ni are not within the above ranges, the 2C discharge capacity of the battery is reduced.
[0108] Particle size screening when the first cathode material is single crystal
[0109] The parameters and test results of the batteries in Examples 29 to 36 are shown in Tables 8 and 9:
[0110] Table 8
[0111]
[0112] Table 9
[0113]
[0114] As can be seen from Table 8, when the first positive electrode material is single crystal and Dv50 is between 0.2 and 10 μm, the battery's 2C discharge capacity is greater than 77%. As can be seen from Examples 35 and 36, when Dv50 is less than 0.2 μm or greater than 10 μm, the battery's 2C discharge capacity is slightly reduced.
[0115] Particle size screening when the first cathode material is secondary particles
[0116] The parameters and test results of the batteries in Examples 37 to 42 are shown in Tables 10 and 11:
[0117] Table 10
[0118]
[0119] Table 11
[0120]
[0121] Table 10 shows that when the first positive electrode material is secondary particles with a Dv50 between 4 μm and 13 μm, the battery's 2C discharge capacity is greater than 93%. Examples 41 and 42 show that when Dv50 is 15 μm, the battery's 2C discharge capacity significantly decreases; when Dv50 is less than 4 μm, the battery's 2C discharge capacity slightly decreases.
[0122] Particle size screening when the second cathode material is single crystal
[0123] The parameters and test results of the batteries in Examples 43 to 47 are shown in Tables 12 and 13:
[0124] Table 12
[0125]
[0126]
[0127] Table 13
[0128]
[0129] It can be seen from Table 13 that the discharge capacity of the battery 2C formed when the particle size of the second positive electrode material is less than 1 μm is better than the discharge capacity of the battery 2C formed when the particle size of the second positive electrode material is greater than 1 μm.
[0130] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0131] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of the technical features being referred to. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. Throughout the description of this application, "plurality" means two or more, unless otherwise specifically defined.
[0132] In this application, unless otherwise expressly specified or limited, terms such as "mounted," "connected," "connect," and "fixed" should be understood in a broad sense. For example, they may refer to fixed connections, detachable connections, or integration; mechanical connections or electrical connections; direct connections or indirect connections through an intermediate medium; and internal connections between two components or interactions between two components. Those skilled in the art will understand the specific meanings of these terms in this application based on specific circumstances.
[0133] In this application, unless otherwise expressly specified or limited, when a first feature is "above" or "below" a second feature, it may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Furthermore, when a first feature is "above," "above," or "above" a second feature, it may mean that the first feature is directly above or diagonally above the second feature, or simply means that the first feature is at a higher level than the second feature. When a first feature is "below," "below," or "below" a second feature, it may mean that the first feature is directly below or diagonally below the second feature, or simply means that the first feature is at a lower level than the second feature.
[0134] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and features of different embodiments or examples without contradiction.
[0135] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A battery, in, include: A first battery cell, the first battery cell comprising a first positive electrode plate, the first positive electrode plate comprising a first positive electrode active layer, and the first positive electrode active layer comprising a first positive electrode material; A second battery cell, wherein the second battery cell comprises a second positive electrode plate, the second positive electrode plate comprises a second positive electrode active layer, and the second positive electrode active layer comprises a second positive electrode material; The first battery cell and the second battery cell are connected in parallel; The first positive electrode material includes a ternary material, and the second positive electrode material includes a lithium-containing phosphate.
2. The battery according to claim 1, in, The number of the first battery cells is x1, the number of the second battery cells is x2, the gram capacity of the first positive electrode sheet in each of the first battery cells is amA·h / g, the gram capacity of the second positive electrode sheet in each of the second battery cells is bmA·h / g, and 0.1≤(b / a) is satisfied 2 (x2 / x1)≤10.
3. The battery according to any one of claims 1 to 2, in, 0.1≤x1 / x2≤10.
4. The battery according to any one of claims 1 to 3, in, 150mA·h / g≤a≤230mA·h / g; and / or 100mA·h / g≤b≤160mA·h / g.
5. The battery according to any one of claims 1 to 4, in, The lithium-containing phosphate includes Li a1 A b1 MP 1-c1 C c1 O 4-d1 D d1 , wherein A includes one or more elements of Group IA elements, M includes VIIB elements and at least one of doping elements of VIIB, C includes one or more elements of Group IIIA elements, Group IVA elements, Group VA elements and Group VIA elements, D includes one or more elements of Group VIA elements and Group VIIA elements, a1 is selected from the range of 0.9 to 1.1, b1 is selected from the range of 0 to 0.1, c1 is selected from the range of 0 to 0.1, and d1 is selected from the range of 0 to 0.
1.
6. The battery according to any one of claims 1 to 5, in, The lithium-containing phosphate includes Li a1 A b1 Mn 1-e1 E e1 P 1-c1 C c1 O 4-d1 D d1 , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W, E includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, C includes one or more elements selected from the group consisting of B (boron), S, Si and N, D includes one or more elements selected from the group consisting of S, F, Cl and Br, a1 is selected from any value in the range of 0.9 to 1.1, b1 is selected from any value in the range of 0-0.100, c1 is selected from any value in the range of 0.001-0.100, d1 is selected from any value in the range of 0.001 to 0.1, and e1 is selected from any value in the range of 0.001 to 0.
5.
7. The battery according to any one of claims 1 to 6, in, The lithium-containing phosphate includes Li 1+x Mn 1-e1 E e1 P 1-c1 C c1 O 4 , wherein 1+x=a1, x is any value in the range of -0.100-0.100, e1 is any value in the range of 0.001-0.500, c1 is any value in the range of 0.001-0.100, and E includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and C includes one or more elements selected from B (boron), S, Si and N.
8. The battery according to any one of claims 1 to 7, in, The second positive electrode material includes a core and a shell covering at least a portion of the surface of the core, and the core includes the lithium-containing phosphate.
9. The battery according to any one of claims 1 to 8, in, The ternary material is Li a2 Ni b2 Co c2 M1 d2 M2 e2 O f2 R′ g2 , where: 0.75 ≤ a2 ≤ 1.2, 0 < b2 < 1, 0 < c2 < 1, 0 < d2 < 1, 0 ≤ e2 ≤ 0.2, 1 ≤ f2 ≤ 2.5, 0 ≤ g2 ≤ 1, f2 + g2 ≤ 3, M1 includes at least one of Mn and / or Al, M2 includes at least one of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R′ includes at least one of N, F, S, Cl.
10. The battery according to any one of claims 1 to 9, in, The ternary material includes at least one of lithium nickel cobalt aluminum oxide and lithium nickel cobalt manganese oxide.
11. The battery according to any one of claims 1 to 10, in, Based on the total mass of the first positive electrode sheet, calculated by mass percentage: Ni 30%~99.5%; Co 3%~49.5%.
12. The battery according to any one of claims 1 to 11, in, The ternary material is a single crystal, and the particle size of the single crystal is 0.2 μm≤D v 50≤10μm, D v 99≤18μm.
13. The battery according to any one of claims 1 to 12, in, The ternary material is a secondary particle formed by agglomeration of primary particles, the particle size of the primary particles is 50nm to 800nm, and the particle size of the secondary particles is 4μm≤D v 50≤13μm, D v 99≤30μm.
14. The battery according to any one of claims 1 to 13, in, The BET of the ternary material is 0.4 to 1.5 m 2 / g.
15. The battery according to any one of claims 1 to 14, in, The second positive electrode material is a single crystal, and the particle size of the second positive electrode material is 50nm-1000nm.
16. The battery according to any one of claims 1 to 15, in, The second positive electrode material is a secondary particle formed by agglomeration of primary particles, and the particle size of the secondary particle is 0.8 μm≤D v 50≤4.2μm, D v 99≤30μm.
17. The battery according to any one of claims 1 to 16, in, The BET of the second positive electrode material is 8 to 20 m 2 / g.
18. An electrical device, in, A battery comprising the battery according to any one of claims 1 to 17.